Selected Topics in Child and Adolescent Mental Health - Stones, Samuel; Glazzard, Jonathan; Rosaria Muzio, Maria (IntechOpen, 2020)
This book addresses a variety of critical themes that relate to child and adolescent mental health and working memory. It focuses on various theoretical perspectives as well as highlighting implications for practice. The topics contemplated include social media and mental health, parent-child interaction therapy (PCIT), the role of e-learning in mental health, perinatal depression and working memory, language, and reading and behaviour. In focusing on mental ill-health, this book addresses a global concern. The causes of poor mental health are complex and multi-faceted. In acknowledging this complexity, it must be recognized that there is no single 'magic bullet' that will solve the problem. A multidisciplinary approach is therefore required for approaching the issues, including a variety of interventions. Finally, the book emphasizes the important contributions that schools, health and social care services and families can provide about addressing the mental health challenges experienced by children and young people.